Attitudes and risky sexual behavior among youth in Kampala, Uganda: Empirical analyses of risk factors by gender - Alaina Whitton; Monica H. Swahn; Rachel Culbreth; Rogers Kasirye (Elsevier, 2022)
Objective: This study sought to examine gender differences and the influence of peer and parental perceptions on sexual risk behaviors among an at-risk sample of youth living in Kampala, Uganda. Methods: Using the cross-sectional Kampala Youth Survey (2014) based in Kampala, Uganda (n = 1134), bivariate and multivariable logistic regressions were conducted to determine the odds of sexual risk behaviors based on peer and parental influence variables and gender. Results: The perceptions of peer, adult, and parental opinions on sexual activity were significantly associated with varying levels across all risky sexual behaviors explored. When indexed and adjusted for other variables, females compared to males were at increased odds of participating in 3-4 risky sexual behaviors (OR: 0.63, 95% CI: 0.44, 0.90) and 5-6 risky sexual behaviors (OR: 0.38, 95% CI: 0.21, 0.68) compared to zero risky sexual behaviors. Conclusions: Adolescent sexual risk behaviors are subject to peer and parental influence and vary between genders. Innovation: This study emphasizes the importance of peer influences in adolescent sexual risk behaviors. Many of these youth are orphans, which may explain the lack of association between parental influences and sexual risk behavior. School-based and community-based interventions may be effective at preventing risky sexual behaviors for this vulnerable population.